Development of a Mentalization-Based Communication Skills Training Package for Adolescent Girls with Self-Injurious Behaviors - Alaeinejad , Neda; Torkan, Hajar; Yousefi , Zahra (Mental Health and Lifestyle Journal, 2025)
The present study aimed to develop a mentalization-based communication skills training package for adolescent girls exhibiting self-injurious behaviors. Therefore, the study employed a mixed-methods research design. The methodology was based on the content analysis approach of Hsieh and Shannon (2005), and the research environment included all texts related to communication skills and mentalization. According to the inclusion and exclusion criteria, ten texts were selected from each category. The criterion for the number of texts was the saturation of qualitative data. Data analysis followed Hsieh and Shannon’s (2005) method for each set of texts. The results of this phase led to the extraction of dimensions, concepts, and sub-concepts for both categories of texts. To design the package, the six-step model proposed by Yousefi and Golparvar (2023) was utilized, leading to the formulation of the structure and content of the training package. The goal of the package was to enhance self-disclosure and empathy as key relationship-sustaining skills through mentalization strategies and techniques. After the development of the package, its content validity was assessed by expert psychotherapists and counselors using the evaluator agreement coefficient. Accordingly, a CVR (Content Validity Ratio) of 0.96 was obtained, indicating strong content validity. Based on these findings, it can be concluded that the mentalization-based communication skills training package possesses content validity as affirmed by experts and is suitable for preliminary implementation to evaluate its practical validity.